Reproductive Growth and Development of Blueberry - Jeffrey G. Williamson; Paul M. Lyrene (EDIS)
This document is HS976, one of a series of the Department of Horticultural Sciences, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Original publication date: April 2004.